Why keep lions instead of livestock? Assessing wildlife tourism‐based payment for ecosystem services involving herders in the Maasai Mara, Kenya. (9th October 2013) - Osano, Philip M.; Said, Mohammed Y.; de, Jan; Ndiwa, Nicholas; Kaelo, Dickson; Schomers, Sarah; Birner, Regina; Ogutu, Joseph O.
Abstract This paper examines the effects of wildlife tourism‐based payments for ecosystem services (PES) on poverty, wealth inequality and the livelihoods of herders in the Maasai Mara Ecosystem in south‐western Kenya. It uses the case of Olare Orok Conservancy PES programme in which pastoral landowners have agreed to voluntary resettlement and exclusion of livestock grazing from their sub‐divided lands. These lands are set aside for wildlife tourism, in return for direct monetary payments by a coalition of five commercial tourism operators. Results show that, on the positive side, PES is the most equitable income source that promotes income diversification and buffers households from the livestock income declines during periods of severe drought, such as in 2008‐2009. Without accounting for the opportunity costs, the magnitude of the PES cash transfer to households is, on average, sufficient to close the poverty gap. The co‐benefits of PES implementation include the creation of employment opportunities in the conservancy and provision of social services. There is however a need to mitigate the negative effects of PES, including the widening inequality in income between PES and non‐PES households and the leakages resulting from the displacement of settlements and livestock to currently un‐subdivided pastoral commons.